Plataformas contables para el fortalecimiento de las microempresas utilizando las Tic (2023)
The study is carried out to frame the importance of accounting systems within micro companies, since these are considerable for their strengthening, from the internal functioning and the value within the market, forcing companies to use the factors accounting and allow their growth.